Artificial intelligence in the field of qualitative marketing research in the Czech Republic - Zámečník, Robert (2025)
Abstract The introduction, use and adoption of artificial intelligence technology has and will probably have serious consequences and impacts in the market research industry. This work brings a view from the perspective of qualitative marketing research on the current problem of artificial intelligence adoption. This work synthesizes the existing literature focused on the adoption of artificial intelligence and available information about artificial intelligence technologies in qualitative marketing research in the form of a systematic literature review. The main objective of this work is to identify factors influencing the adoption of technologies using artificial intelligence in qualitative marketing research in the Czech Republic. The target group for the research is decision makers of qualitative marketing research commissioners. Both quantitative and qualitative research were used to examine the objectives. One of the main findings is that the more useful, and easy to use the AI application is perceived by the target audience, the more it will be adopted. It was also found that the fear factor and apprehension about this new technology plays an important role in its adoption. The main theoretical contribution of this work is the real application of The Technology Acceptance Model (TAM) theory and a partial theoretical extension of this model in the field of artificial intelligence adoption in qualitative marketing research with a possible practical contribution usable within the marketing research community.